E-learning - an interventional element of the PRiVENT project to improve weaning expertise - Michels-Zetsche, Julia D.; Schubert-Haack, Janina; Tanck, Katrin; Neetz, Benjamin; Iberl, Gabriele; Müller, Michael; Kempa, Axel; Joves, Biljana; Rheinhold, Andreas; Ghiani, Alessandro; Tsitouras, Konstantinos; Schneider, Armin; et al. (BMC medical education, 2024)
PRiVENT (PRevention of invasive VENTilation) is an evaluation of a bundle of interventions aimed at the prevention of long-term invasive mechanical ventilation. One of these elements is an e-learning course for healthcare professionals to improve weaning expertise. The aim of our analysis is to examine the implementation of the course in cooperating intensive care units.